AIM in Medical Education - Davids,J; Lam,K; Nimer,A; Gianarrou,S; Ashrafian,H (2022)
Artificial intelligence (AI) is making a global impact on various professions ranging from commerce to healthcare. This section looks at how it is beginning and will continue to impact other areas such as medical education. The multifaceted yet socrato-didactic methods of education need to evolve to cater for the twenty-firstcentury medical educator and trainee. Advances in machine learning and artificial intelligence are paving the way to new discoveries in medical education delivery. Methods This chapter begins by introducing the broad concepts of AI that are relevant to medical education and then addresses some of the emerging technologies employed to directly cater for aspects of medical education methodology and innovations to streamline education delivery, education assessments, and education policy. It then builds on this to further explore the nature of new artificial intelligence concepts for medical education delivery, educational assessments, and clinical education research discovery in a PRISMAguided systematic review and meta-analysis. Results Results from the meta-analysis showed improvement from using either AI alone or with conventional education methods compared to conventional methods alone. A significant pooled weighted mean difference ES estimate of ES 4.789; CI 1.9-7.67; p 1/4 0.001, I2 1/4 93% suggests a 479% learner improvement across domains of accuracy, sensitivity to performing educational tasks, and specificity. Significant amount of bias between studies was identified and a model to reduce bias is proposed. Conclusion AI in medical education shows considerable promise in domains of improving learners’ outcomes; this chapter rounds off its discussion with the role of AI in simulation methodologies and performance assessments for medical education, highlighting areas where it could augment how we deliver training.